2023
DOI: 10.1186/s12913-023-09325-7
|View full text |Cite
|
Sign up to set email alerts
|

eHealth policy framework in Low and Lower Middle-Income Countries; a PRISMA systematic review and analysis

Abstract: Background Low and lower middle-income countries suffer lack of healthcare providers and proper workforce education programs, a greater spread of illnesses, poor surveillance, efficient management, etc., which are addressable by a central policy framework implementation. Accordingly, an eHealth policy framework is required specifically for these countries to successfully implement eHealth solutions. This study explores existing frameworks and fills the gap by proposing an eHealth policy framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Meaningful use of EHRs requires EHR capabilities that include, among other things, patient portals, patient-monitoring system, and computerized provider order entry (CPOE) as discussed earlier. Leveraging advanced use, EHRs hold great promise to improve poor health outcomes and health equity [ 9 , 10 , 71 ]. The Medicaid Promoting Interoperability Program has greatly contributed to the uptake of technology in clinical care practices in the U.S., as nearly 9 out of 10 offices have adopted a basic EHR system [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meaningful use of EHRs requires EHR capabilities that include, among other things, patient portals, patient-monitoring system, and computerized provider order entry (CPOE) as discussed earlier. Leveraging advanced use, EHRs hold great promise to improve poor health outcomes and health equity [ 9 , 10 , 71 ]. The Medicaid Promoting Interoperability Program has greatly contributed to the uptake of technology in clinical care practices in the U.S., as nearly 9 out of 10 offices have adopted a basic EHR system [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Florida specifically the majority of Medicaid providers do not use the EHR system to their full capabilities [ 30 ]. Our study provides critical insights into the structural barriers (regional, local, economic, and resource-related issues) that hinder the optimal diffusion of health IT for low-resourced providers [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also tried to avoid the drawbacks of cloud computing, particularly the lack of security and privacy, by introducing an innovative security framework based on chain ontology. Also, in Mengiste et al [40], researchers have pointed out the reasons for the inefficiency of e-health models published in several works. Their study identified the key elements influencing an efficient e-health policy framework and discovered a gap in the context of developing nations, and proposed a fourstep e-health policy implementation guideline for effective e-health implementation in the context of developing countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This review reveals that while the adoption of digital health technologies has gradually increased among older adults, uptake remains varied across demographic groups and intervention types. Facilitators like perceived usefulness, social influences, and ease of use can promote adoption [50,71,72]. However, barriers spanning technological challenges, limited accessibility, lack of awareness, and concerns over privacy and trust persist, especially among disadvantaged groups [73][74][75].…”
Section: Digital Health Adoption Patternsmentioning
confidence: 99%
“…Managerial support, training, and workflows integrating technologies into routine care are key facilitators [71]. Global policy frameworks also emphasize the need for coordinated deployment and capacity building for eHealth [72].…”
Section: Implementing Digital Health In Healthcare Systemsmentioning
confidence: 99%